Magnetic properties of Cu doped CeO2 nanostructures prepared by microwave refluxing technique. Issue 6 (15th April 2018) - Alla, S.K.; Kollu, P.; Mandal, R.K.; Prasad, N.K.
Abstract: Spherical as well as rod shaped Cux Ce1−x O2 ( x = 0.01, 0.03 and 0.05) nanostructures were produced by microwave refluxing technique. The shape of the particles were identified by transmission electron microscopy (TEM) analysis. The prevalence of surface oxygen vacancies and progressive increase of their concentration with increased Cu content have been identified by Raman and PL spectroscopy analysis. Magnetic measurements have shown room temperature ferromagnetic (RTFM) behavior for the samples and their MS values were 0.0027, 0.012 and 0.001 A m 2 /kg for x = 0.01, 0.03 and 0.05 respectively. The relatively smaller MS values for these samples as compared to undoped sample may be attributed to the presence of anti-ferromagnetic interactions amongst Cu-ions. The sudden rise in the MS value for x = 0.03 could be due to the presence of ferromagnetic clusters in the sample.